2004
DOI: 10.1089/end.2004.18.865
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of Renal Candidiasis

Abstract: Renal candidial infections have been described in the literature in susceptible populations of all age groups. Systemic antifungal agents have been successful in treating these patients, but in the presence of an obstructed kidney, antegrade (perurethral) or retrograde (percutaneous) drainage of the pelvicaliceal system is mandatory to salvage the kidney. An aggressive percutaneous endoscopic approach for the management of such a case in a young diabetic patient with multiple comorbidities is described here wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Fungus balls are an uncommon complication of Candida UTI except in neonates, in whom fungus ball formation in the collecting system commonly occurs as a manifestation of disseminated candidiasis [483]. In adults, surgical or endoscopic removal of the obstructing mycelial mass is central to successful treatment [94,508,509]. In neonates, some series documented resolution of fungus balls with antifungal treatment alone [510], but others found that endoscopic removal was necessary [511,512].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Fungus balls are an uncommon complication of Candida UTI except in neonates, in whom fungus ball formation in the collecting system commonly occurs as a manifestation of disseminated candidiasis [483]. In adults, surgical or endoscopic removal of the obstructing mycelial mass is central to successful treatment [94,508,509]. In neonates, some series documented resolution of fungus balls with antifungal treatment alone [510], but others found that endoscopic removal was necessary [511,512].…”
Section: Evidence Summarymentioning
confidence: 99%
“…Aggressive surgical debridement is required in addition to systemic treatment with amphotericin (with or without flucytosine) or fluconazole (24,55,167). Debulking of the fungal mass and aggressive local irrigation with amphotericin and even streptokinase could be considered as an adjunct to systemic antifungal therapy if a percutaneous device provides direct access (17,53,227). Percutaneous nephrostomies can relieve the obstruction initially and also permit irrigation with antifungals (19).…”
Section: Treatment Of Candiduriamentioning
confidence: 99%
“…Intermittent saline irrigation, percutaneous endoscopic disruption and drainage, and percutaneous irrigation with streptokinase can also be performed to facilitate the breakdown and passage of fungus balls [62,63]. The recommended dose is 0.3 to 1.0 mg/kg per day for 5 to 7 days, but even a single-dose with 0.2 to 1.0 mg/kg has been shown to be effective [64].…”
Section: Treatment Of Complicationsmentioning
confidence: 99%